Penanaman Sikap Cinta terhadap Rasul dengan Mengamalkan Kitab Al Barzanji di Desa Kampung Gili - Muhammad Ichsan Fauzi; Wirani Atqia (Pendidikan Agama Islam STIT Palapa Nusantara, 2021)
This study aims as an effort to describe: (1) Cultivating an attitude of love towards the apostle by practicing the book of Al Barzanji in the village of Kampung Gili, Kabupaten Batang (2) The obstacle in this research is the lack of interest in the village community of Kampung Gili Kabupaten Batang. The stem of the attitude of love in the book of Al Barzanji. (3) In this research, the researcher uses the case study method. Case studies were chosen because research requires in-depth, intensive, and detailed information about certain events at the individual level, group of people, or organizations so that the resulting data are accurate data related to the research being conducted. This research was conducted at the Nurul Jannah Council, precisely in the village of Kampung Gili Kab. Batang in June 2021. The data in this study were obtained from interviews with the ustadz of the Nurul Jannah assembly and one of the students from the Nurul Jannah assembly of Kampung Gili Kabupaten Batang.The results of this study indicate that the village of Kampung Gili instills an attitude of love for the apostle by practicing the book of Al Barzanji. Berzanji is a book created by Sheikh Ja'far Al Barzanji. In this study, the reading was carried out after the maghrib prayer at the Nurul Huda assembly in Kmapung Gili village every Friday night. In the routine of reading the book of Al Barzanji at the Nurul Huda assembly, Kampung Gili Kab.Batang This stem was followed by the students of the Nurul Huda assembly under the guidance of Ustadz Nurul Huda assemblies. The media that are often used in this routine are: Kitab Al Barzanji, Sound system, and Kitab Kitab (Dampar). In this study, it produced data that the ustadz in this assembly guided the children during the routine reading of the book of Al Barzanji in the Nurul Jannah assembly in the village of Kampung Gili Kabupaten Batang.In this study, it is expected that the students of the santri really practice the attitude of morality in accordance with what is contained in the book of Al Barzanji. By practicing what is contained in the book of Al Barzanji so that the students themselves will get used to doing good things that are in accordance with the morals of the Prophet, which is contained in the book of Al Barzanji.